Gender and Crime: Addressing Threats to Construct Validity in the Criminological Research (Global Journal of Human-Social Science, 2014)
In this article, we argue that criminology is in need of a meta-theory that allows for a more complete treatment of the gender-crime relationship. We suggest that one such metatheory is Integral Theory. Integral Theory challenges disciplinary myopia and opens space for a more complete treatment of complex constructs such as gender. We note that criminology would benefit from an ontological and epistemological pluralismthat accommodates the wide range of existing gender theories and recognizes the value of multiple methods designed to test those theories. These arguments are supported via an analysis of recent research on the gender-crime relationship.
Keywords: gender; criminology; construct validity; integral theory; meta-theory; gender and crime; methodological pluralism